2012
DOI: 10.1371/journal.pmed.1001196
|View full text |Cite
|
Sign up to set email alerts
|

No Treatment versus 24 or 60 Weeks of Antiretroviral Treatment during Primary HIV Infection: The Randomized Primo-SHM Trial

Abstract: In a three-arm randomized trial conducted among adult patients in HIV treatment centers in The Netherlands, Marlous Grijsen and colleagues examine the effects of temporary combination antiretroviral therapy during primary HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 42 publications
7
66
0
1
Order By: Relevance
“…Finally, our results suggest that an early treatment slowing down viral replication during the initial phase of the infection should be beneficial because it gives the immune system time to develop its full breadth. This could explain why early treatment during primary HIV infection can result in decreased viral setpoints and be very beneficial (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results suggest that an early treatment slowing down viral replication during the initial phase of the infection should be beneficial because it gives the immune system time to develop its full breadth. This could explain why early treatment during primary HIV infection can result in decreased viral setpoints and be very beneficial (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…A series of prior studies have indeed shown that short-term antiretroviral treatment in acute or early HIV-1 infection can preserve B-cell-mediated (6) and T-cellmediated (7) immune function, supports the development of HIV-1-specific CD4 T cell responses (8), limits the diversity of circulating viral strains (9), and in some cases facilitates spontaneous control of low-level HIV-1 viremia after treatment discontinuation (10,11). Recently, data from three prospective, randomized-controlled clinical trials indicated that a 1-to 2-year antiretroviral treatment course started during acute or early HIV-1 infection can lead to reduced HIV-1 set point viremia after treatment discontinuation (12)(13)(14), providing compelling evidence for beneficial effects of antiretroviral therapy initiation dur-ing the earliest stages of HIV-1 infection. Nevertheless, such effects were modest and not sustained long term, indicating that short-term therapy in primary infection may not significantly affect the eventual HIV-1 disease outcome.…”
mentioning
confidence: 99%
“…21,32,37,40 Duration of ART at PHI Three randomised controlled trials in PHI reported a modest benefit (delaying the decline in CD4 cell count, or time from PHI, to requiring lifelong ART) following a 48-week 38 or 60-week 39,40 course of ART. Interruption of therapy even if started close to the time of PHI is no longer recommended.…”
Section: 36mentioning
confidence: 99%